Friends like this: The impact of the US–China trade war on global value chains - Haiou Mao; Holger Görg (The World Economy, 2020)
This paper considers the indirect impact the recent tariff increases between the United States and China can have on third countries through links in global supply chains. We combine data from input–output relationships, imports and tariffs, to calculate the impact of the tariff increases by both the United States and China on cumulative tariffs paid by third countries. We show that the tariff hikes increase cumulative tariffs for other countries and thus hurt trade partners further downstream in global supply chains. We also show that this is particularly important for tariff increases on Chinese imports in the United States. These are likely to be used as intermediates in production in the United States, which are then re-exported to third countries. The most heavily hit third countries are the closest trade partners, namely the EU, Canada and Mexico. We estimate that the tariffs impose an additional burden of around 500 million to 1 billion US dollars on these countries. China's tariffs on US imports have less of an effect.
Keywords: 330; cumulative tariffs; indirect tariffs; trade war